Os propósitos estratégicos do Tribunal de Contas do Estado de Pernambuco: desafios para a sua realização à luz das novas tendências da administração pública no Brasil - Sousa, Edgard Távora de (2008)
The Court of Auditors for the State of Pernambuco (know as TCE-PE), during its strategic planning process, realized its need to be recognized by Pernambuco society as an effective instrument in the improvement of public management. This objective is present in its mission statement and in its strategic vision, as declared in the Strategic Plan for the 2008- 2012 period. Withing its pages, we can verify that it is not only the effectiveness of TCE-PE's institutional results that needs to be recognized by society. What we look forward to is that all the results from public management, within its jurisdiction, are also effective. In other words, our goal is to have TCE-PE intervene in Pernambuco's public management sphere in order to improve it, or for it to become more effective. Along the way, some variables will act in its favor, facilitating, while others will act in against it, complicating the attainment of this strategic binomial. The goal of this research is to identify, from the point of view of a management variable, which are the institutional and organizational elements that facilitate or complicate this process.